Reaksi Pasar Modal Akibat Pengumuman Kasus Positif Pertama Virus Covid-19 Varian Omicron Di Indonesia - Dewi, Ni Kadek Sintya; Darmayanti, Ni Putu Ayu; Suarjaya, Anak Agung Gede (E-Jurnal Akuntansi, 2023)
The capital market reaction to an announcement or event containing information is an important thing for investors to pay attention to. Important information for investors to know for future decision making. This research aims to determine the capital market reaction caused by the announcement of the first positive case of the Omicron variant of the Covid-19 virus in Indonesia on December 16 2021. This research uses the event study method with a 7 day research period. The research sample was taken using the Slovin technique from 80 companies that are members of the Kompas100 Index. The hypothesis test used in this research is the One Sample T-test. The results of this research show that there is no market reaction as indicated by the insignificant abnormal returns obtained around the announcement event. The results of this research indicate that the capital market in Indonesia can take the form of an informationally efficient, semi-strong market. Keywords: Market Capital Reaction; Abnormal Return; Omicron Virus; Efficient Market Hypothesis; Signaling Theory